EVALUASI DAYA DUKUNG WISATA DI TAMAN WISATA ALAM SANGEH, BALI - I Putu Hindu Iswara; I Komang Gede Santhyasa (UNHI PRESS, 2021)
The TWA Sangeh area was established based on the Decree of the Minister of Forestry Number SK.203 / Menhut-II / 2014 dated 03 March 2014 concerning the Sangeh Natural Park Area (RTK.21) covering an area of ​​13.91 hectares in Badung Regency, Bali Province, with two functions namely the conservation function and cultivation function, the carrying capacity in the TWA sangeh area is an important point for the sustainability of these two functions so that they coexist well. Identifying the tourism carrying capacity that can be accommodated in TWA Sangeh, and identifying the role of the management of the TWA Sangeh area on tourism carrying capacity are the objectives of this study using quantitative and qualitative methods. Capability The carrying capacity of tourists at TWA Sangeh in supporting visitor activity on a tour is determined by the calculation of the physical carrying capacity (PCC), real carrying capacity (RCC), and the effective carrying capacity of the ECC. The capacity of the carrying capacity provides a less than optimal picture of this being an opportunity for tourism development in TWA Sangeh.